Motor Vehicles: Are they emerging threats to Lake Victoria and its environment? - Awange, Joseph; Obera, B. (Springer, 2007)
Lake Victoria and its basin supports more than 30 million people, while its fishes are exported the world over. This second largest fresh water body is however experiencing stress due to eutrophication, sedimentation, declining levels and more recently the motor vehicle sector. This contribution examines the general pollution from motor vehicle and gives an in-depth analysis of motor vehicle washing along the lakeshore. The results indicate the water samples from the motor vehicle washing and urban runoff points to be slightly acidic (i.e., average pH of 6.7) and average Total at these points. The conductivity for the motor vehicle washing points averaged at 150 S/cm, while the urban runoffs point was more varied ranging from below 150 S/cm to over 400 S/cm (average 301 S/cm). A positive correlation coefficient of more than 0.7 is obtained between the total daily count of vehicles and each of the water quality parameter tested. This signifies a strong correlation between motor vehicle related activities and the pollution of the lake. In general, the motor vehicle industry is found to have a noticeable negativeeffect on the lake.